CIRCULATORY CYTOKINES AND HEMATOLOGICAL PROFILES: POSSIBLE BIOMARKERS OF HIV/AIDS DISEASE PROGRESSION - Mugwe, Jane N; Gicheru, Michael M; Mwatha, Joseph (LIFE: International Journal of Health and Life-Sciences, 2019)
Introduction: This study sought to identify circulatory cytokines and hematological profiles measureable in blood plasma in newly diagnosed HIV patients as possible biomarkers that could predict the progression of HIV and AIDS disease in the course of acute HIV infection.Methodology: A prospective cross sectional study design was used to recruit the participants at the Nakuru Provincial General hospital in Kenya. The study group included those who were HIV positive before and after commencing therapy and those who were HIV negative. The study group composed of male and female of different ages ranging from 7-72 years. Hematology auto analyzer system was used to analyze hematological parameters and indices. Types and concentrations of cytokines were determined using multiplex cytokine immunoassay by flow cytometry using Becton and Dickinsonfluorescence activated cell sorter (BD FACS) count. Descriptive statistics were applied and a p- value < 0.05 was considered statistically significant.Results: This study found a significant difference in mean Interleukin 12p70 (p<0.001), Tumor Necrosis Factor (p<0.05), Interleukin 10 (p<0.05), Interleukin 6 (p<0.005) and interleukin 1β (p<0.05) between HIV negative patients, treatment naïve HIV patients and HIV patients on highly active antiretroviral therapy (HAART). Among the treatment naïve HIV patients, significant associations were observed between IL-12p70 and HGB (p<0.05); between TNF and MPV (p<0.001); between IL-10 and PDW (p<0.005); between IL-6 and Gran# (p-0.05); between IL-1β and PDW (p<0.005).Conclusion: The early period of infection with HIV is characterized by high circulatory cytokines levels and could be useful biomarkers and indicators of early immune activation of HIV infection. The results from this study also showed that acute HIV infection induces several hematological changes, involving all the blood parameters and indices, some of which may act as indicators of HIV/AIDS disease progression.